China's Human Rights Approach to International Crimes; Case Studies of Myanmar - Maryam Zarekhanmohammadi; ‌ Roohollah Talebi Arani (رهیافتهای سیاسی و بین المللی)
Introduction: With the onset of reforms and opening up in 1978, the People's Republic of China entered a new era. This period transcended mere economic miracle, exerting broad transnational influence and culminating in the emergence of a global power. the People's Republic of China has taken an active, extensive, and multifaceted role in the international governance of human rights by maintaining the fundamental principles of the Communist Party with Chinese characteristics. The main question is how the People's Republic of China's approach to human rights has shaped its response to international human rights violations in Myanmar. We hypothesize that the People's Republic of China's dual approach to international human rights discourse in the framework of the communist-Leninist ideology creates a delicate balance between the triad of politics (sovereignty as a right and non-intervention), culture (the principle of cultural relativism) And the economy (fostering development and social stability) has shaped the country's direct and indirect response to human rights violations in Myanmar. Methods: To investigate the causes and dimensions of the People's Republic of China's approach to the human rights crisis of the Rohingya Muslim minority in Myanmar during 2016 and 2017, We employed a matching test for intra-case analysis within our case study research method. This allowed us to examine why a government in the international system takes an approach in the face of the human rights crisis in another government, which not only accepts and appeases it but also continues and expands relations in various dimensions. Results and discussion: Our findings indicate that the human rights approach of the People's Republic of China to the crisis of the Rohingya Muslim minority has been influenced by the complex and mutual interactions of various political, cultural, and economic factors while balancing the maintenance of domestic ideological values and norms with the pursuit of international benefits. While China's macroeconomic investments of the People's Republic of China in Myanmar, particularly in energy, have brought important benefits to this country, they also created a conflict of interest regarding international human rights obligations and their legitimacy in the international system. Conclusion: The People's Republic of China's response to the human rights abuses against the Rohingya minority in Myanmar during 2016 and 2017 was twofold. On the one hand, the statesmen of the People's Republic of China at the international level, especially in front of the United Nations Security Council, have tried to provide comprehensive support to the Myanmar government and the army of this country, relying on the importance of national sovereignty and the principle of non-interference, and even international sanctions against this prevent the country. On the other hand, in the framework of regional cooperation, in the role of a responsible great power, it has wanted a peaceful solution to this crisis through a peaceful approach based on dialogue diplomacy. the People's Republic of China's double reaction can be seen as the result of the delicate balance that China has established between maintaining national interests and adhering to international obligations as a permanent member of the United Nations Security Council.Keywords: International Crimes, China's Human Rights Approach, Communist Ideology, Myanmar Crisis, Rohingya.